The Monongahela tradition in "real time": Bayesian analysis of radiocarbon dates. - John P Hart; Bernard K Means (PLoS ONE, 2022)
Despite advances in techniques, methods, and theory, northeastern North American archaeologists continue to use early to mid-twentieth century culture historical taxa as units of analysis and narrative. There is a distinct need to move away from this archaeological practice to enable fuller understandings of past human lives. One tool that enables such a move is Bayesian analysis of radiocarbon dates, which provides a means of constructing continuous chronologies. A large dataset of radiocarbon dates for late prehistoric (ca AD 900/1000-1650) sites in the lower upper Ohio River basin in southwestern Pennsylvania and adjacent portions of Maryland, Ohio, and West Virginia is used here as an example. The results allow a preliminary assessment of how the settlement plans of contemporaneous villages varied considerably, reflecting decisions of the village occupants how to structure built environments to meet their needs.